Development Need Analysis of U-Career Application in Choosing Department at Vocational High Schools - Farida Aryani; Muhammad Rais; Hamdan Arfandy (Journal of Educational Science and Technology (EST), 2021)
The purpose of this study is (1) to determine the level of need for guidance and counseling teachers in developing U Career applications for students in SMK (2) To determine the validity and practicality of U Career applications to help students choose majors in SMK. The approach used in this study is the Research and Development (R & D) approach which is designed to produce an Android-based U-career application product for students in SMK. The targets in this study were 13 guidance and counseling teachers from 5 districts/cities in South Sulawesi. Data collection techniques used questionnaires (validity and acceptability assessment questionnaires for testing guidance and ICT experts and prospective users of BK products/teachers) and focus group discussions (FGD). The data analysis technique used descriptive percentage analysis. The results of this study indicate that (1) Guidance and counseling teachers assess the use of the U Career application as very important for vocational students to help them choose majors in SMK (2) the U Career application reaches a valid and practical category to be used by students in choosing majors in SMK. Thus the U Career Application product can assist BK teachers in implementing career guidance services based on the talents, interests, and potential of vocational students.